« Culture for the million, or society as it may be » - Françoise Baillet (Cahiers Victoriens et Edouardiens, 2010)
When in the late nineteenth century Aestheticism slowly lost ground to the Arts and Crafts Movement and then to Decadence and Art Nouveau, the Victorian artistic field had considerably evolved. Freed from the moral task traditionally assigned to it, English art now claimed its autonomy — « All art is quite useless » wrote Wilde in the Preface to The Picture of Dorian Gray in 1891 —, relying on a pictorial idiom which, in time, had become quite familiar to a large public. The purpose of this paper is to examine the role and function of the graphic arts in the Victorians’ familiarity with avant-garde theories. At a time when the demands of an enlarged readership triggered a remarkable development of periodical literature, the illustrated press was partly responsible for the circulation of the very ideals it meant to ridicule. From the vantage point offered by such publications as The Illustrated London News and, of course, Punch, cartoons became the missing link between highbrow and lowbrow culture, thus contributing to the long-lasting fascination exerted by Aestheticism on the rest of society.